BIMBINGAN DAN PELATIHAN PENYUSUNAN PENCATATAN KEUANGAN DALAM PENGELOLAAN USAHA KECIL - Rena Feri Wijayanti; Joni Dwi Pribadi; Yosi Afandi; Lina Budiarti; Musthofa Hadi (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2018)
Small businesses are one of the drivers of the Indonesian economy. In addition for having characteristics, small business also has several factors that are a limiting factor for small business to grow and develop. One of these problems is related to financial management where the recording of each transaction that has been carried out is the basis for evaluating activities and assesing the succes of a business.